Long‐term psychosocial outcomes after nondirected donation: A single‐center experience. Issue 5 (31st December 2018) - Jacobs, Cheryl; Berglund, Danielle M.; Wiseman, Jennifer F.; Garvey, Catherine; Larson, Dawn B.; Voges, Margaret; Radecki Breitkopf, Carmen; Ibrahim, Hassan N.; Matas, Arthur J.
Abstract : Short‐term studies have demonstrated that nondirected donors (NDDs) have psychosocial outcomes that are similar to donors who donate directly, but long‐term studies have not been done. NDDs at our center were surveyed regarding motivation; support during donation; stress related to donation; regret; financial resources used for donation; preferences about communication with the recipient; and cost reimbursement. Of 100 NDDs who donated at our center in the last 20 years, 95 remain in contact with us, and 77 responded to our survey (mean ± standard deviation [SD] 6.7 ± 4 years postdonation). The most common motivation for donation was the desire to help another (99%). Many NDDs received support from family, friends, and employers. NDDs voiced stress about the possibility of recipient kidney rejection, physical consequences to themselves, and financial burden. Only one donor expressed regret. Almost half wanted some recipient information at donation; 61% preferred routine recipient status updates; 56% believed meeting the recipient should occur at any mutually agreeable time; and 55% endorsed reimbursement for expenses. Stressors for NDDs are analogous to those of directed donors; NDDs prefer having some information about the recipient and prefer to be given a choice regarding the timing for communication with the recipient. NDDs supported donation being financially neutral. Abstract : Long‐term psychosocial outcomes after nondirected donation: A single‐center experience